Prospección de la incidencia en la calidad ambiental, de la implementación de la infraestructura del proyecto de "Ganadería De Leche" en la Parroquia Pasa, provincia de Tungurahua. Plan de manejo ambiental 2015. - Guevara Morales, Carmen Rocío (2016)
All activities of the human being have an impact at the environmental, economic and social level. This is one of the biggest concerns for the “Unión de Organizaciones Campesinas e Indígenas de PasaUOCAIP”. In order to promote activities in harmony with the nature, they have implemented a livestock project in line with the current legislation. The aim of this plan is to conduct a research about the consequences of the project “Dairy cattle” in terms of environmental quality. The project took place in Pasa, in the Ambato Canton situated in Tungurahua Province and it utilized a particular technique based on observation, integrated with a documentary analysis, visits in the field, meetings with the project’s proposer, the support of a bibliographic review and specific instruments implemented in the project. In order to control the negative impact on the environment (in particular on air, water and soil), prevention and mitigation instruments were considered by the project and they were linked with the implementation phase. It was exactly in this context that el “environmental management and listing” was written, and as a result, the environmental license was obtained, contributing in this way, with the livestock project in Pasa, to the development in a frame that is economically viable, socially equitable and environmentally responsible.